SOFTWARE AND ITS TYPES, STRUCTURE, STRUCTURE. MODERN PROGRAMMING LANGUAGES (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Software is the second most important part of a computer, which includes a set of data processing programs and documents necessary for the use of a computer. In this article, software and its types and modern programming languages ​​are discussed. information is provided.